ANALISA KETENTUAN KESELAMATAN KERJA PADA KONTRAK KONSTRUKSI FIDIC BUKU MERAH 2017 - Gusman Simon (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2023)
Occupational accidents in the construction sector have a very significant contribution. One of the constructive efforts that can be carried out is to apply the Occupational Health and Safety provisions as stated in the construction contract. Among the various construction contract formats, the FIDIC Red Book 2017 contains several Occupational Health and Safety provisions in its clauses which can be used as a reference for Employers and Contractors in terms of risk sharing and scope of responsibility. The research aims to describe the Occupational Health and Safety provisions in the 2017 Red Book FIDIC construction contract format and compare them with applicable national regulations. From an analysis of the contents of sub-clauses that are relevant to Occupational Health and Safety and a comparison with the regulation of the Minister of PUPR Number 10 of 2021 concerning guidelines for construction safety management systems, an insight into the contents of the 2017 Red Book FIDIC sub-clauses regarding Occupational Health and Safety, in general, has been included in the regulation of the Minister of PUPR Number 10 of 2021. FIDIC itself prioritizes Contractor compliance with applicable national regulations. Among the provisions of Occupational Health and Safety in the FIDIC Red Book 2017 and the regulation of the Minister of PUPR Number 10 of 2021 are compatible and mutually reinforcing.Keywords: Comparison of Clauses; FIDIC; Occupational Health and Safety